ECG and echocardiography processing for decision support in heart failure - Emmanouilidou, Dimitra (Computing in Cardiology Conference, 2008)
This paper presents an effective way to achieve a high level integration of signal and image processing methods in the general management of heart failure, by means of a clinical decision support system (CDSS). In particular, significant and suitably designed image and signal processing algorithms are introduced to objectively and reliably evaluate important features that can facilitate decisional problems in collaboration with the CDSS. Architectural details of the components of the CDSS needed for the seamless integration of image and signal analysis work-flows are finally discussed.